PENGARUH CITRA COGNITIVE TERHADAP KUNJUNGAN DI SAWARGILOKA WATERLAND CIAPUS - Wildan Rizky Rahadian (Politeknik Harapan Bersama, 2023)
Abstract The purpose of this study was to determine the effect of cognitive image on the tourist’s decision visit in Sawargiloka Waterland Ciapus. This study was designed with a quantitative approach and accidental sampling as a sampling technique to obtain data by using a questionnaire as a data collection tool. As for testing the effect of the variables studied, the author uses a simple linear analysis technique. From the test results, it was found that the coefficient of determination (R2) is 71.2. Which is shows that there was an influence of tourist facilities and service quality on tourist’s visit decision, while the other 28.8% were variables that were not included in the study. The implication of this research is that the management of Sawargiloka Waterland Ciapus needs to improve the physical aspects so that it can create a good cognitive image for tourists. Keyword: cognitive image, decision visitation, tourist